Enhanced catalytic activity of Sm/CeO2 to produce gasoline-range hydrocarbons from pyrolysis of spent coffee grounds - Kassa Dada, Tewodros (Elsevier, 2024)
This study investigated the application of Sm/CeO2 catalyst for hydrocarbon production in catalytic pyrolysis (CP) of spent coffee grounds (SCGs). A temperature range of 450–750 °C and catalyst/biomass (C/B) ratios of 0.5–4 were employed in the CP. The results showed that an increase in pyrolysis temperature consistently increased the quantity of hydrocarbons and considerably decreased the oxygenated compounds like acids and phenols. At temperatures of 450 and 550 °C, C/B ratios of 2 or 1 generated the maximum amount of hydrocarbons. At 650 and 750 °C temperatures, C/B ratios of 0.5 and 1 were capable to achieve a higher content of hydrocarbons in bio-oils, suggesting the synergistic effect of temperature and catalyst activity. The hydrocarbons in bio-oils were found in the gasoline range, mainly containing benzene, toluene, ethylbenzene, xylene (BTEX), olefins, and cycloalkenes. Primary reactions involved to convert oxygenated compounds into hydrocarbons were dehydration, decarboxylation, decarbonylation, dehydrogenation, isomerization, and aromatization reactions.